A magnetic nanomaterial for antibody purification, preparation method and application thereof
By preparing Fe3O4@SiO2@APTMS@PIDA-Ni2+ magnetic nanomaterials, the problems of insufficient biocompatibility, stability and selectivity of cured carriers in existing antibody purification technologies are solved, and efficient and reversible protein immobilization and antibody purification effects are achieved.
Patent Information
- Application Number
- CN202411437987.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-10-15
AI Technical Summary
In the existing antibody purification technology, the biocompatibility, stability and selectivity of the curing carrier are insufficient, and blocking of protein active sites is difficult to avoid.
By preparing Fe3O4@SiO2@APTMS@PIDA-Ni2+ magnetic nanomaterial, the material modified the long chain bicarboxylic structure on the surface, bound Ni2+, to specifically bind to the histidine tag on mycoplasma protein, achieving high selectivity and reversible binding ability.
This magnetic nanomaterial has high biocompatibility, stability and selectivity, can effectively immobilize protein M without destroying its active site, and can be reused, suitable for the purification and rapid detection of antibodies.
Smart Images

Figure CN118955696B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of antibody purification reagents, and in particular to a magnetic nanomaterial for antibody purification, a preparation method and application thereof. Background Art
[0002] Antibodies play an important role in modern drug development technology. Over the past 30 years, antibodies have been used to treat or diagnose a variety of different diseases. Antibodies are produced by B cells on the plasma membrane and have a similar structure, consisting of two heavy chains and two light chains. The production of recombinant antibodies faces many challenges. These modifications include: recombinant expression, purification and possible post-translational modifications. The purification of recombinant antibodies is one of the most important production steps, and the purification effect directly affects the final application.
[0003] To date, many antibody purification systems based on antibody binding proteins have been constructed for antibody purification, such as protein A, protein G, protein L and protein M. Among them, protein M has an obvious advantage over other antibody binding proteins: it can bind to both κ and λ chains at the same time, and can be widely applied to immunoglobulin G (IgG), immunoglobulin (IgA), immunoglobulin M (IgM) and its derivatives such as antigen binding fragment (Fab), bivalent antibody fragment F(ab′)2 or single-chain variable fragment (scFv), but protein M is the least studied of all antibody binding proteins because when protein M was discovered, it was shown that its binding to antibodies was irreversible or required very harsh conditions.
[0004] In order to improve protein stability, activity and reusability, protein immobilization technology has been applied to different fields, such as biocatalysis, toxin adsorption, biosensing and other important industries. Traditional immobilization materials include nanoparticles (NPs), nanoflowers (NFs), porous carbohydrate-based materials, covalent organic frameworks (COFs) and metal organic frameworks (MOFs). However, the above-mentioned immobilization materials all have the following problems: low biocompatibility, poor stability and difficulty in separation from the system. At the same time, it is difficult to control how to prevent the solid materials from blocking the active sites of the protein in the application of the above-mentioned materials.
[0005] Regarding magnetic nanomaterials, China's invention patent application No. 2024105132405 discloses a method for preparing Fe3O4@SiO2@EDTA-PDA magnetic nanomaterials, which prepares Fe3O4 nanoparticles with a core-shell structure for extracting malachite green from samples. However, the above-mentioned magnetic nanomaterials, after chelating EDTA-PDA, are prone to ion exchange with antibodies and destroy the structure of the antibodies.
[0006] Therefore, how to design a protein-immobilized carrier that does not block the active sites of the protein and at the same time has high biocompatibility, good stability and is easy to separate from the system is an urgent problem to be solved by technicians. Summary of the invention
[0007] The present invention provides a magnetic nano material for antibody purification, a preparation method and its application. The magnetic nano material has the advantages of strong ability to load mycoplasma protein, no toxicity to mycoplasma protein and easy control of the position of protein on the surface of the magnetic nano material.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] A magnetic nanomaterial for antibody purification is prepared by reacting the following compounds by weight: 5.0-6.0 g of FeCl3·6H2O, 2.5-3 g of FeCl2·4H2O, 25-28 g of NH3·H2O, 0.85-1 g of 3-aminopropyltrimethoxysilane, 1.4-2 g of tetraethyl silicate, 1-1.3 g of sodium chloroacetate, 0.72-0.75 g of triethylamine and 0.5-0.6 g of NiSO4·6H2O.
[0010] When used, the nanomaterial has good monodispersity, biocompatibility, high selectivity and environmental responsiveness, and high protein loading capacity. After separating the target, the nanomaterial can be reused by further desorption.
[0011] Preferably, the magnetic nanomaterial comprises, by weight, 5.4 g of FeCl3·6H2O, 2.98 g of FeCl2·4H2O, 27 g of NH3·H2O, 0.9 g of 3-aminopropyltrimethoxysilane, 1.5 g of tetraethyl silicate, 1.28 g of sodium chloroacetate and 0.5 g of NiSO4·6H2O.
[0012] The present invention also provides a method for preparing the magnetic nanomaterial, which comprises the following steps:
[0013] Synthesis of S01 and Fe3O4 nanoparticles
[0014] Dissolve FeCl3·6H2O and FeCl2·4H2O in deionized water to obtain a mixed solution;
[0015] Under argon protection, ammonia water was slowly added dropwise to the mixed solution, and stirred at 250 rpm for 10-12 h at 60-65 °C to obtain crude Fe3O4 nanoparticles;
[0016] The crude Fe3O4 nanoparticles were collected by an external magnet, washed with deionized water until neutral, and then washed with 50% ethanol solution for 10-15 times, and vacuum dried at 60 °C for 12-24 h to obtain Fe3O4 nanoparticles;
[0017] Synthesis of S02 and Fe3O4@SiO2
[0018] Fe3O4 nanoparticles were dispersed in ethanol, and deionized water and ammonia were added. 1.5 mL of tetraethyl silicate was added dropwise under ultrasonic conditions at room temperature for 30 min, and then ultrasonicated for another 15 min.
[0019] The mixture obtained above was stirred at 300 rpm at 25 °C for 12 h to obtain a crude Fe3O4@SiO2 product;
[0020] The crude Fe3O4@SiO2 was collected by an external magnet, washed with deionized water for 10-15 times, and vacuum dried at 60 °C for 12 h to obtain Fe3O4@SiO2;
[0021] Synthesis of S03, Fe3O4@SiO2–APTMS
[0022] Fe3O4@SiO2 was dispersed in toluene, 3-aminopropyltrimethoxysilane was added dropwise, and the mixture was refluxed at 95 °C for 12 h under argon protection to obtain a crude Fe3O4@SiO2–APTMS product;
[0023] The crude Fe3O4@SiO2–APTMS was collected by an external magnet, washed with pure methanol for 3–5 times, and dried under vacuum at 60 °C for 12 h to obtain Fe3O4@SiO2–APTMS;
[0024] S04, Fe3O4@SiO2–PIDA–Ni 2+ Synthesis
[0025] The obtained Fe3O4@SiO2-APTMS was dispersed in a mixed solution of ethanol and triethylamine in which sodium chloroacetate was dissolved, and refluxed at 80°C for 12 h under argon protection to obtain a crude Fe3O4@SiO2-PIDA product;
[0026] The crude Fe3O4@SiO2-PIDA was washed with pure methanol and deionized water for 5-10 times to obtain Fe3O4@SiO2-PIDA;
[0027] Fe3O4@SiO2-PIDA was dispersed in NiSO4·6H2O solution and shaken at 25℃ for 12 h to obtain Fe3O4@SiO2–PIDA–Ni 2+ crude product;
[0028] Fe3O4@SiO2–PIDA–Ni 2+ The crude product was washed with deionized water for 3-5 times to obtain pure Fe3O4@SiO2–PIDA–Ni 2+ , that is, the magnetic nanomaterial is obtained.
[0029] Preferably, in step S01, the stirring temperature is 60°C.
[0030] Preferably, in step S01, the stirring time is 12 h.
[0031] Preferably, in step S01, the vacuum drying time is 12 h.
[0032] The present invention also provides the application of the magnetic nanomaterial, specifically as follows (1) or (2) or (3):
[0033] (1) As an immobilized carrier of mycoplasma proteins;
[0034] (2) As a reagent for purifying IgG antibodies, Fab antibodies and scFv antibodies;
[0035] (3) As a rapid antibody test kit.
[0036] Compared with the prior art, the advantages or beneficial effects of the technical solution of the present application include:
[0037] 1. Traditional silicon-based magnetic beads use the silicon hydroxyl groups on the surface to interact with proteins, but the binding area is not selective, and has poor stability, low binding ability, irreversible immobilization, and destroys protein activity. The present invention modifies the long-chain dicarboxyl structure on the silicon base through the prepared magnetic nanoparticles. 2+ After binding, it can specifically bind to the histidine tag on the mycoplasma protein, with high selectivity and reversible binding ability.
[0038] 2. Traditional hydroxyl and amino magnetic beads will destroy protein activity. The present invention converts all the silanol groups on the surface of the magnetic beads into dicarboxyl groups and uses Ni 2+ Combined with dicarboxyl groups, the surface of the prepared magnetic beads does not contain groups that affect protein activity, and PIDA provides a long-chain flexible structure, which makes it easier to capture mycoplasma proteins in complex environments, thereby achieving high selectivity and loading rate.
[0039] 3. The nanomaterial prepared in the present application can be used for immobilization reaction of protein M. Protein M is different from traditional protein A, protein G, and protein L because after protein M adsorbs antibodies after solidification, it cannot be desorbed, while other proteins do not have such problems. Therefore, the prepared nanomaterial and the treated protein M have the characteristics of linkage and synergistic enhancement. It not only achieves the goal of not destroying the functional sites of protein M after immobilization, but also enables protein M to be used as an adsorption agent for separating antibodies. After the antibodies are adsorbed, they can also be desorbed smoothly, thereby having the functions of adsorption and desorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Flowchart for nanomaterial preparation;
[0041] Figure 2 The structural and morphological characteristics of Fe3O4 superparamagnetic nanoparticles;
[0042] Figure 3 The crystal structure and purity statistics of Fe3O4 and its modified products;
[0043] Figure 4 It is the statistical diagram of the decomposition rate of Fe3O4 and its modified products;
[0044] Figure 5 It is the statistical diagram of the loading capacity of MNiNP;
[0045] Figure 6 This is the repeatability analysis diagram of MNiNP;
[0046] Figure 7 This is the storage stability analysis diagram of MNiNP. DETAILED DESCRIPTION
[0047] The following will describe the implementation methods of the present application in detail with reference to the accompanying drawings and embodiments, so that the implementation process of how the present application applies technical means to solve technical problems and achieve corresponding technical effects can be fully understood and implemented accordingly. The embodiments of the present application and the various features in the embodiments can be combined with each other without conflict, and the technical solutions formed are all within the protection scope of the present application.
[0048] It should be clear that the embodiments described below are only part of the embodiments of this application, rather than all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by technicians in the relevant field without making creative work are within the scope of protection of this application.
[0049] Example 1 (Preparation of Nanomaterial-NiNP)
[0050] This embodiment discloses a magnetic nanomaterial for antibody purification and a preparation method thereof, specifically:
[0051] 1. Reagents.
[0052] Ferric chloride hexahydrate (FeCl3·6H2O, ≥99.0%), ferrous chloride tetrahydrate (FeCl2·4H2O, ≥99.5%), ammonia (NH3·H2O, 25.0–28.0%), 3-aminopropyltrimethoxysilane (APTMS, 99.0%), tetraethyl silicate (TEOS, ≥99.0%), and sodium chloroacetate (≥99.0%) were purchased from Shanghai MacLean Biochemical Co., Ltd. (Shanghai, China). Nickel sulfate hexahydrate (NiSO4·6H2O, AR) and isopropyl-β-D-thiogalactopyranoside (IPTG, ≥99.0%) were purchased from Aladdin Co., Ltd. (Shanghai, China). All organic solvents were of analytical grade and used without further purification.
[0053] 2. Synthesis of Fe3O4 nanoparticles.
[0054] Synthesized by coprecipitation method, 5.4 g FeCl3·6H2O and 2.98 g FeCl2·4H2O were dissolved in 100 mL deionized water in a 250 mL three-necked flask. Under argon protection, 25 mL ammonia water was slowly added to the solution, stirred at 250 rpm for 12 h at 60°C, Fe3O4 nanoparticles were collected by external magnet, washed with deionized water until neutral, and washed with 50% ethanol solution for 10-15 times. Stored in 50% ethanol solution, vacuum dried at 60°C for 12 h, and used for later use.
[0055] 3. Synthesis of Fe3O4@SiO2.
[0056] Fe3O4@SiO2 was prepared by sol-gel method. 0.5 g Fe3O4 nanoparticles were dispersed in 50 mL ethanol in a 100 mL three-necked bottle, 10 mL deionized water and 2.5 mL ammonia water were added, and 1.5 mL LTEOS (tetraethyl silicate) was added dropwise under ultrasonic conditions at room temperature for 30 min, and then ultrasonicated for 15 min. Finally, the obtained mixture was stirred at 300 rpm at 25 °C for 12 h. Fe3O4@SiO2 was magnetically separated and washed with deionized water for 10-15 times. Fe3O4@SiO2 was stored in deionized water, dried under vacuum at 60 °C for 12 h, and then used.
[0057] 4. Synthesis of Fe3O4@SiO2–APTMS.
[0058] The preparation method of Fe3O4@SiO2-APTMS is as follows: 0.5 g Fe3O4@SiO2 is dispersed in 16 mL toluene in a 50 mL three-necked flask, 0.85 mL APTMS is added dropwise, and refluxed at 95°C for 12 h under argon protection. After magnetic separation, Fe3O4@SiO2-APTMS is washed with pure methanol for 3-5 times. Fe3O4@SiO2-APTMS is stored in pure methanol, dried under vacuum at 60°C for 12 h, and then used.
[0059] 5. Fe3O4@SiO2–PIDA–Ni 2+ synthesis.
[0060] Fe3O4@SiO2-PIDA was synthesized by dispersion method in a 50 mL three-necked flask. 0.5 g of Fe3O4@SiO2-APTMS was dispersed in a solution of 15 mL of ethanol and 10 mL of triethylamine dissolved in 1.28 g of sodium chloroacetate. Fe3O4@SiO2-PIDA was obtained by reflux at 80 °C for 12 h under argon protection, and washed with pure methanol and deionized water for 5-10 times, respectively. 0.5 g of Fe3O4@SiO2-PIDA was dispersed in 20 mL of 0.1 M NiSO4·6H2O solution and shaken at 25 °C for 12 h. The resulting Fe3O4@SiO2–PIDA–Ni 2+ Wash with deionized water for 3-5 times, store in 20% ethanol as a suspension (0.1 g / mL) for later use. 2+ , denoted as NiNP.
[0061] Example 2 (Preparation of Immobilized Protein-MMNiNP)
[0062] This example discloses the steps for preparing immobilized protein M.
[0063] Expression and purification of protein M.
[0064] Expression and purification of protein M mutants. Transform the pET28a-M-8his plasmid into E. coli BL21 (DE3). Spread the colonies on LB plates containing 50 μg / mL kanamycin and incubate at 37°C overnight. Pick a single colony and transfer it to 5 mL of culture medium (LB) containing 50 μg / mL kanamycin and incubate it at 37°C, 200 rpm overnight. Then, transfer the culture to 200 mL of 2YT medium (5.0 g / L sodium chloride, 10 g / L yeast extract, 16 g / L peptidone) and incubate until OD 600At 0.5-0.6, isopropyl-β-D-thiogalactoside (inducer, IPTG) (62.5 μL, 0.8M) was added to promote induction, and incubated at 20°C, 200 rpm for 16-18h. The cells after induced expression were collected by centrifugation, centrifuged at 8000 rpm, 4°C for 10 min, and the bacterial cells were resuspended in binding buffer (5 mM imidazole buffer, pH 7.7). The cells were lysed by a high-pressure homogenizer at 600 bar for 5-7 min. The cell lysate was centrifuged at 8000 rpm, 4°C for 1 h, and the supernatant protein solution was collected. Filtered with a 0.22 μm filter, the Ni-NTA-agarose column was pre-calibrated with 2 column volumes of binding buffer. Washed with 5 column volumes of wash buffer (20 mM imidazole buffer, pH 7.7), and finally eluted with elution buffer (250 mM imidazole buffer, pH 7.7). The purity was determined by SDS-PAGE, and the concentration was determined by the Bradford method (Coomassie Brilliant Blue method).
[0065] 2. Immobilization and elution of protein M on NiNPs.
[0066] In order to immobilize the protein M mutant on NiNP, NiNP was washed several times with deionized water, protein M binding buffer, and 5mM imidazole buffer (pH 7.7). 500 μL protein M cell lysate of 8 samples and 5 mg NiNP were ultrasonicated at 4°C for 5-40 min to obtain immobilized M protein (MNiNP) at different times. MNiNP is used to represent immobilized M protein.
[0067] The MNiNPs were separated by an external magnet, washed multiple times with washing buffer, and stored in phosphate buffered saline solution (PBS buffer solution) (pH 7.7) to detect the loading / loading rate and reusability of MNiNPs for protein M.
[0068] MNiNPs were separated by an external magnet, washed with deionized water and 20% ethanol solution, and stored as a suspension (0.1 mg / mL) in 20% ethanol solution. The purity of the eluate was determined by SDS-PAGE, and its concentration was determined by Bradford method.
[0069] Example 3 (Application example of MNiNP purification of antibodies)
[0070] 1. Expression and purification of trastuzumab scFv.
[0071] Expression of trastuzumab scFv. Transform the pET28a-trastuzumab scFv plasmid into E. coli BL21 (DE3). Spread the colonies on LB plates containing 50 μg / mL kanamycin and incubate at 37°C overnight. Take one colony and transfer it to 5 mL LB containing 50 μg / mL kanamycin and incubate it at 37°C, 200 rpm overnight. Then, transfer the culture to 400 mL LB medium and grow it in two 500 mL flasks until OD 600 When the culture concentration reached 0.5-0.6, IPTG (50 μL, 0.8 M) was added to promote induction, and the cells were incubated at 25°C and 200 rpm for 14-16 h. The cells after induced expression were collected by centrifugation, centrifuged at 8000 rpm at 4°C for 10 min, and the bacterial cells were resuspended in binding buffer (5 mM imidazole buffer, pH 7.7). The cells were homogenized at 300 bar under high pressure in a high-pressure homogenizer for 5 min, and the cell lysate was centrifuged at 8000 rpm at 4°C for 1 h to collect the supernatant protein solution, which was filtered with a 0.22 μm filter and 5 mg MNiNP was added to 1 mL of deionized water in a 1.5 mL centrifuge tube. The suspension was divided into 8 parts and incubated at 4°C for different times (5-40 min) with regular shaking (once every 5-7 min). The immobilized trastuzumab scFv was magnetically separated and eluted with 0.8 mL of citric acid buffer (0.1 M, pH 3.5-6) at room temperature for 5 min. Subsequently, the MNiNPs were separated by an external magnet, and the pH value of the elution solution was immediately calibrated to 7.4-7.6 by adding an appropriate amount of Tris-HCl (1 M, pH 8.5). The antibody purity was detected by SDS-PAGE, and the antibody concentration was determined by the Bradford method.
[0072] 2. Purification of S2P6 and 76E1.
[0073] The purification process of S2P6 IgG, Fab, 76E1 IgG and Fab was as follows: 300 μL of cell lysate was mixed with 5 mg of MNiNP in a 1.5 mL centrifuge tube. The suspension was incubated at 4 °C for different times (20-80 min) with regular shaking (every 5-7 min). The cell lysate was then separated and the MNiNP containing the immobilized antibody was washed 3-4 times with 1 mL of PBS (pH 7.2-7.4). The washing step was necessary because IgGs and Fabs contained significant concentrations of bovine serum albumin (BSA) in the cell lysate. The antibodies were then eluted with 200 μL of citrate buffer (0.1 M, pH 4.5) for 5 min at room temperature with gentle shaking. The MNiNP was separated with an external magnet and the pH of the eluted solution was immediately calibrated to 7.4-7.6 by adding 45 μL of Tris-HCl (1 M, pH 8.5). The antibody purity was checked by SDS-PAGE and the antibody concentration was determined by Bradford assay. Example 4
[0074] MNiNP and antibody loading capacity calculation:
[0075] The MNiNP and antibody loading capacity was calculated by Equation 1.
[0076] (1)
[0077] Where Qe (mg g −1 ) is the loading capacity of MNiNP, V (L) represents the total volume of elution, Co-Ct represents the elution concentration of protein M or antibody in mg / L, and m (g) represents the mass of MNiNP. Example 5
[0078] This example tests the stability of MNiNPs.
[0079] A 0.1 g / mL MNiNP suspension was stored in PBS (50 mM, pH 7.4) for 15 days. Every 3 days, 5 mg of MNiNPs were taken, washed with deionized water and trastuzumab scFv binding buffer, and dispersed in 1 mL of trastuzumab scFv cell lysate. The suspension was incubated at 4 °C for 30 min with regular shaking (every 5-7 min). The immobilized trastuzumab scFv was magnetically separated and gently eluted with 0.8 mL of citric acid buffer (0.1 M, pH 4.5) for 5 min at room temperature. The MNiNPs were then separated with an external magnet, and the pH of the eluted solution was immediately calibrated to 7.4 by adding an appropriate amount of Tris-HCl buffer solution (1 M, pH 8.5). The MNiNPs were washed 3 times with PBS (50 mM, pH 7.4) and stored in the same buffer. The Bradford method was used to determine the antibody concentration, and the concentration of the trastuzumab eluate on day 0 was taken as 100%, indicating that MNiNPs had good stability and were not easily decomposed. Example 6
[0080] This example tests the reusability of MNiNPs.
[0081] The reproducibility test of MNiNPs was performed using trastuzumab purification. Specifically, 5 mg of MNiNPs were washed with deionized water and trastuzumab scFv binding buffer and dispersed in 1 mL of trastuzumab scFv cell lysate. The suspension was incubated at 4°C for 30 min with regular shaking (every 5-7 min). The immobilized trastuzumab scFv was magnetically separated and gently eluted with 0.8 mL of citric acid buffer (0.1 M, pH 4.5) for 5 min at room temperature. The MNiNPs were then separated using an external magnet and the pH of the elution solution was immediately calibrated to 7.4 by adding an appropriate amount of 1M Tris-HCl buffer solution (pH 8.5). The MNiNPs were immediately washed three times with PBS buffer (50 mM, pH 7.4) and repeated 10 times using the same MNiNPs. The antibody concentration was determined using the Bradford method. The concentration of the trastuzumab eluate in the first cycle was taken as 100%.
[0082] in conclusion:
[0083] 1. Synthesis and modification of magnetic beads.
[0084] Fe3O4 was synthesized by coprecipitation method. Figure 1 A silicon dioxide layer Fe3O4@SiO2 was added to its surface by a sol-gel process, and an amine coating was formed by APTMS. Sodium chloroacetate was used to replace the amine group to convert it into a PIDA structure Fe3O4@SiO2-PIDA with chelating ability, which was further combined with Ni 2+Fe3O4@SiO2-PIDA-Ni was obtained by activation 2+ , stored in a 20% ethanol solution in the form of a suspension for later use.
[0085] 2. Representation.
[0086] Figure 2 Fe3O4 superparamagnetic nanoparticles are shown, the nanoparticle cores are spherical, almost monodisperse, and have an average diameter of 15.9 nm.
[0087] The crystal structure and purity of Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2-APTMS and Fe3O4@SiO2-PIDA were determined by XRD method, such as Figure 3 shown.
[0088] Interpretation: The Fe3O4 XRD pattern is very consistent with the standard cubic structure of Fe3O4, see the figure in PDF # 88-0866. The peaks at 2θ = 18.4°, 30.1°, 35.5°, 37.0°, 43.2°, 53.4°, 57.0° and 62.7° are (111), (220), (311), (222), (400), (422), (511) and (440), respectively. The presence of amorphous silica in the structure is confirmed by the obvious diffuse peaks at 2θ = 15-25° for Fe3O4@SiO2, Fe3O4@SiO2-APTMS and Fe3O4@SiO2-PIDA. The patterns of Fe3O4@SiO2-APTMS and Fe3O4@SiO2-PIDA are very similar to those of Fe3O4@SiO2, so it can be concluded that the modification of APTMS and PIDA does not lead to the loss of crystallinity of the core structure.
[0089] Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2-APTMS, Fe3O4@SiO2-PIDA and Fe3O4@SiO2-PIDA-Ni 2+ The decomposition rate of Figure 4 shown.
[0090] Interpretation: Fe3O4 only lost 2.41% of its total weight due to the removal of adsorbed water molecules. After SiO2 modification, the overall weight loss increased to 3.87%, APTMS, PIDA and Ni 2+ The weight of the derivatives decreased more significantly at temperatures above 200 °C.
[0091] 3. The loading capacity of MNiNP was evaluated and compared with that of commercial Ni-NTA agarose resin chromatography filler. MNiNP had a higher maximum loading capacity of 74.41 mg / g at a fixed time of 25 min. While the results of Ni-NTA agarose resin were more stable, the loading capacity was lower with a maximum loading capacity of 49.01 mg / g. It should also be noted that MNiNP showed very high positional specificity for protein M and no washing was required before the elution step. Ni-NTA agarose resin, on the other hand, required extensive washing (3-5 CV with washing buffer). The results are shown in Figure 5 shown.
[0092] 4. The reproducibility and storage stability of MNiNP are important parameters. MNiNP showed high reusability. After 4 consecutive cycles, the binding capacity of MNiNP and scFv was 90.5% of the initial capacity in the first cycle. Figure 6 This may once again prove the stability of protein M on NiNP and the effectiveness of active sites. Figure 7 The storage stability analysis of MNiNPs over 15 days is shown. MNiNPs were stored in PBS solution (50 mM, pH 7.4) at 4°C. After 15 days of storage, the ability of MNiNPs to capture scFv from cell lysate was still equal to 76.1% of the initial capacity at day 0.
Claims
1. A magnetic nanomaterial for antibody purification, characterized in that: The invention is prepared by reacting the following compounds by weight: 5.0-6.0 g of FeCl3·6H2O, 2.5-3 g of FeCl2·4H2O, 25-28 g of NH3·H2O, 0.85-1 g of 3-aminopropyltrimethoxysilane, 1.4-2 g of tetraethyl silicate, 1-1.3 g of sodium chloroacetate, 0.72-0.75 g of triethylamine and 0.5-0.6 g of NiSO4·6H2O; The preparation method of the magnetic nanomaterial comprises the following steps: Synthesis of S01 and Fe3O4 nanoparticles Dissolve FeCl3·6H2O and FeCl2·4H2O in deionized water to obtain a mixed solution; Under argon protection, ammonia water was slowly added dropwise to the mixed solution, and stirred at 250 rpm for 10-12 h at 60-65 °C to obtain crude Fe3O4 nanoparticles; The crude Fe3O4 nanoparticles were collected by an external magnet, washed with deionized water until neutral, and then washed with 50% ethanol solution for 10-15 times, and vacuum dried at 60 °C for 12-24 h to obtain Fe3O4 nanoparticles; Synthesis of S02 and Fe3O4@SiO2 Fe3O4 nanoparticles were dispersed in ethanol, and deionized water and ammonia were added. 1.5 mL of tetraethyl silicate was added dropwise under ultrasonic conditions at room temperature for 30 min, and then ultrasonicated for another 15 min. The mixture obtained above was stirred at 300 rpm at 25 °C for 12 h to obtain a crude Fe3O4@SiO2 product; The crude Fe3O4@SiO2 was collected by an external magnet, washed with deionized water for 10-15 times, and vacuum dried at 60 °C for 12 h to obtain Fe3O4@SiO2; Synthesis of S03, Fe3O4@SiO2–APTMS Fe3O4@SiO2 was dispersed in toluene, 3-aminopropyltrimethoxysilane was added dropwise, and the mixture was refluxed at 95 °C for 12 h under argon protection to obtain a crude Fe3O4@SiO2–APTMS product; The crude Fe3O4@SiO2–APTMS was collected by an external magnet, washed with pure methanol for 3–5 times, and dried under vacuum at 60 °C for 12 h to obtain Fe3O4@SiO2–APTMS; S04, Fe3O4@SiO2–PIDA–Ni 2+ Synthesis The obtained Fe3O4@SiO2-APTMS was dispersed in a mixed solution of ethanol and triethylamine in which sodium chloroacetate was dissolved, and refluxed at 80°C for 12 h under argon protection to obtain a crude Fe3O4@SiO2-PIDA product; The crude Fe3O4@SiO2-PIDA was washed with pure methanol and deionized water for 5-10 times to obtain Fe3O4@SiO2-PIDA; Fe3O4@SiO2-PIDA was dispersed in NiSO4·6H2O solution and shaken at 25℃ for 12 h to obtain Fe3O4@SiO2–PIDA–Ni 2+ crude product; Fe3O4@SiO2–PIDA–Ni 2+ The crude product was washed with deionized water for 3-5 times to obtain pure Fe3O4@SiO2–PIDA–Ni 2+ , that is, the magnetic nanomaterial is obtained.
2. The magnetic nanomaterial for antibody purification according to claim 1, characterized in that: By weight, it includes 5.4 g of FeCl3·6H2O, 2.98 g of FeCl2·4H2O, 27 g of NH3·H2O, 0.9 g of 3-aminopropyltrimethoxysilane, 1.5 g of tetraethyl silicate, 1.28 g of sodium chloroacetate and 0.5 g of NiSO4·6H2O.
3. The magnetic nanomaterial for antibody purification according to claim 1, characterized in that: In step S01 , the stirring temperature is 60°C.
4. The magnetic nanomaterial for antibody purification according to claim 1, characterized in that: In step S01, the stirring time is 12 h.
5. The magnetic nanomaterial for antibody purification according to claim 1, characterized in that: In step S01, the vacuum drying time is 12 h.
6. The use of the magnetic nanomaterial according to claim 1, characterized in that: is as follows (1) or (2), (1) As a reagent for purifying IgG antibodies, Fab antibodies and scFv antibodies; (2) As a protein immobilization carrier.